Applications of label‐free, quantitative phase holographic imaging cytometry to the development of multi‐specific nanoscale pharmaceutical formulations. Issue 5 (30th March 2017) - Luther, Ed; Mendes, Livia P.; Pan, Jiyai; Costa, Daniel F.; Torchilin, Vladimir P.
Abstract: A label‐free, high content, time‐lapse holographic imaging system was applied to studies in pharmaceutical compound development. Multiple fields of cellular images are obtained over typically several day evaluations within standard CO2 incubators. Events are segmented to obtain population data of cellular features, which are displayed in scattergrams and histograms. Cell tracking is accomplished, accompanied by Cartesian plots of cell movement, as well as plots of cell features vs. time in novel 4‐D displays of X position, Y position, time, and cell thickness. Our review of the instrument validation data includes 1) tracking of Giant HeLa cells, which may be undergoing neosis, a process of tumor stem cell generation; 2) tracking the effects of cell cycle related toxic agents on cell lines; 3) using MicroRNAs to reverse the polarization state in macrophages to induce tumor cell killing; 4) development of liposomal nanoformulations to overcome Multi‐Drug Resistance (MDR) in ovarian cancer cells; and 5) development of dual sensitive micelles to specifically target matrix metalloproteinase 2 (MMP2) over‐expressing cell lines. © 2017 International Society for Advancement of Cytometry